POLA JARINGAN KOMUNIKASI PADA KELOMPOK TANI : ANALISIS JARINGAN PADA KELOMPOK TANI WIRESINGE, KECAMATAN NARMADA KABUPATEN LOMBOK BARAT TAHUN - , Eka Putri Paramita, Dr. Phil. Ana Nadya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Communication is a process that is unavoidable in life of the groups, especially farmers. Many development programs conducted by the government adoption of innovation-based approach that relies heavily on the group. so it becomes important to know about the communication patterns are formed in a farmer group. This study aims to describe patterns of communication network and a sociogram to give an overview of communication activities in seeking and sharing fertilizer related information among members of farmer group or members of farmer group with other information sources within the Batukuta village, Narmada sub-district, West Lombok. The study used a combination of quantitative and qualitative Methods. Analysis used is the communication network analysis which allows to determine the pattern of communication networks that are formed in the communication process within Wiresinge farmer group. The UCInet package was used to analyse communication networks typology. The results showed that the dissemination of information about fertilizers in Wiresinge farmers' group done through the communication network at the group level. From the analysis there were 17 people known to be a source of information. Patterns of communication networks that are formed in the process of searching for information in the group is wheel typology. Similarly, when group members share information distribution network following the typology of the wheels, through a network of important roles in communication networks such as bridges, liaison, isolate and opinion leaders. These roles were chosen by the members of farmer groups with regard to social status, education, occupation, age and gender. In the process of finding and sharing information in Wiresinge farmers' group the opinion leaders are the one who serves as chairman of that group as well as a religious leader. Chairman of the group is considered as someone who has lots of information and can be trusted. Thus, in every communication pattern group leaders are always at the center of the network.